2022
DOI: 10.1007/s00394-022-02919-7
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey

Abstract: Purpose The COVID-19 pandemic and public measures have a direct impact on the nutrition situation; studies show changes in food consumption, eating behavior or body weight but complex pattern analyses of changes rarely exist. Methods During the first German lockdown, a web-based survey was conducted among adults. It included 33 questions about changes in food intake, eating habits and physical activity, as well as anthropometrics and sociodemographic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 53 publications
2
21
1
Order By: Relevance
“…Moreover, the intervention phase of our study fell within the first and second lockdowns of the COVID-19 pandemic in Germany in 2020. During this period, the level of psychological distress increased, and vulnerable people engaged more often in dysfunctional eating patterns (ie, EE) [ 104 ]. In addition, many people were affected by short-term work or job losses and subsequent income losses [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the intervention phase of our study fell within the first and second lockdowns of the COVID-19 pandemic in Germany in 2020. During this period, the level of psychological distress increased, and vulnerable people engaged more often in dysfunctional eating patterns (ie, EE) [ 104 ]. In addition, many people were affected by short-term work or job losses and subsequent income losses [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, those with worsened diet quality also had worsened dietary consciousness on both scales. In a previous study, those who changed their eating pattern to a health-oriented pattern during COVID-19 were paying more attention to the consumption of healthy foods than individuals who practiced emotion-driven eating behavior [ 23 ]. Another study showed that those with a high perception of the importance and precedence of diet were more likely to have been involved in home cooking during the COVID-19 pandemic [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in food intake during the lockdown period due to the COVID-19 pandemic have also been reported in several countries [ 6 , 10 , 20 , 21 ]; however, most previous studies have examined changes by the food group and related factors. Only a few studies have evaluated changes in diet quality on an individual basis [ 22 , 23 ]. In Tribst et al’s study [ 22 ], increased time spent on eating activities was positively associated with improved diet quality (IDQ) but negatively related to worsening diet quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic has exacerbated disparities and rendered the already serious educational crisis worsened. Although the schools were opened in the vast majority of countries during the Omicron variant period because of the implementation of health protocols and immunization programs, the effects on learning, health, well-being, and dropout rates were severe [8] Staying at home for a long time may also result in their eating patterns and physical activity [10]. The anxiety and stress produced by the lockdown may result in a change in sleeping pattern, disrupted sleep because of overstimulation, and/or nightmares [11].…”
Section: Introductionmentioning
confidence: 99%